THE CHARACTERISTICS OF AUTISM ASPERGER SYNDROME IN MARK HADDON’S NOVEL THE CURIOUS INCIDENT OF THE DOG IN THE NIGHT - Dhitya Anggreni; M. Manugeren (JOURNAL OF LANGUAGE, 2019)
This article is concerned with the protagonist of the story suffering from Asperger Syndrome. He finds difficulty in social interaction, be it appearance, language, attitude, or thinking. In addition, he has got an intelligent ability to interpret objects around him well. He has also the ability to make patterns of activities that he does every time. The whole analysis is conducted by means of qualitative research method supported by library research. The grand theory used is on autism, picturing Asperger Syndrome as an autism spectrum disorder on the high functioning end; referred to as “dash of autism”. Asperger syndrome, also known as Asperger’s, is a developmental disorder characterized by significant difficulties in social interaction and nonverbal communication, along with restricted and repetitive patterns of behavior and interests. The results show that the protagonist of the novel has got some significant features of Asperger Syndrome: Lacking of Social Activity, Ability of Interpreting Object, and Ability to Set Routine Patterns.